Multifaceted empathy differences in children and adults with autism - Jennifer M. Quinde-Zlibut (Nature Portfolio, 2021)
Abstract Although empathy impairments have been reported in autistic individuals, there is no clear consensus on how emotional valence influences this multidimensional process. In this study, we use the Multifaceted Empathy Test for juveniles (MET-J) to interrogate emotional and cognitive empathy in 184 participants (ages 8–59 years, 83 autistic) under the robust Bayesian inference framework. Group comparisons demonstrate previously unreported interaction effects between: (1) valence and autism diagnosis in predictions of emotional resonance, and (2) valence and age group in predictions of arousal to images portraying positive and negative facial expressions. These results extend previous studies using the MET by examining differential effects of emotional valence in a large sample of autistic children and adults with average or above-average intelligence. We report impaired cognitive empathy in autism, and subtle differences in emotional empathy characterized by less distinction between emotional resonance to positive vs. negative facial expressions in autism compared to neurotypicals. Reduced emotional differentiation between positive and negative affect in others could be a mechanism for diminished social reciprocity that poses a universal challenge for people with autism. These component- and valence- specific findings are of clinical relevance for the development and implementation of target-specific social interventions in autism.